Pharmacotherapy of disorders of central nervous system function in gynecological practice as a problem of adaptation disorders correction - Бурчинский, С. Г. (REPRODUCTIVE ENDOCRINOLOGY, 2016)
Currently, in the developed countries 30–45% of the population suffering from sleep disorders or insomnia, which indicates a high prevalence and social significance of the insomnia problem. At menopause syndrome and premenstrual dysphoric syndrome insomnia occur in 60–80% of cases, significantly affecting the psychological state and quality of women’s life, causing formation of the neurotic, cerebrovascular, cardiac and other diseases. This is largely due to the development of circadian rhythm disorders are closely associated with neuroendocrine factors. Sleep hormone melatonin is a major factor for humoral regulation of sleep-wake cycle, and one of the key factors determining the adaptive capacity of the central nervous system and the whole organism. As a natural chronobiotic synchronizing circadian biorhythms, melatonin provides a normalization of various aspects of the central nervous system, derived from the equilibrium state. In clinical practice this is reflected in the presence of hypnogenic effect of melatonin, which serves as a basis for leading the clinical indications for its use – insomnia of different nature. Melatonin is characterized by the combined chronotropic, anxiolytic, antidepressant and cognitive effects are not peculiar to any other neuro- and psychotropic drugs. In many clinical studies melatonin confirmed the efficacy and safety as a hypnotic, adaptogen and control functions of the central nervous system. Melatonin provides sleep as close to reality as possible. Melatonin is characterized by a high safety level, a complete lack of postsomnic syndrome and psychomotor disorders, as well as the risk of addiction and dependence. In patients with insomnia during treatment with melatonin there were reduction of emotional lability, anxiety, depression, improve mood, increase clarity of consciousness, short-term memory improvement, reducing fatigue, increasing social activity. Among the melatonin preparations present in Ukraine, special attention should be paid for drug vita-melatonin, which fully complies with all international quality standards and the most economically accessible.